Economic and Socio-Demographic Effects of Global Climate Change - Artem S. Lukyanets; Sergey V. Ryazantsev (International Journal of Economics and Financial Issues, 2016)
The article discusses the main challenges and threats of global climate change and their impact on economic and socio-demographic processes in the countries most exposed to climate change. In world politics the topic of global climate change is not new, and every year more countries participate in international programs to reduce the impact of climate change on social, economic, demographic and even geopolitical processes. The problem of climate change is not local in nature and affects the entire group of countries and even continents. According to the intergovernmental group of experts of the UNPO, in the period 1880 to 2012, global average temperatures have risen by 0.85 degrees Celsius (The official website of UNPO, 2015). At the same time, every year more and more countries feel the consequences of climate change. According to the world organization for migration, in 2014, more than 19,3 million people were forced to change their place of permanent residence in connection with climatic factors (Gemenne et al., 2015). The loss of the world economy is measured in billions of US dollars.